AAV6.βARKct cardiac gene therapy ameliorates cardiac function and normalizes the catecholaminergic axis in a clinically relevant large animal heart failure model - Raake, Philip; Schlegel, Philipp; Reinkober, Julia; Barthelmes, Jens; Schinkel, Stefanie; Pleger, Sven Torsten; Mier, Walter; Haberkorn, Uwe; Katus, Hugo; Most, Patrick; Müller, Oliver J. (European heart journal, 2013)
Aims: G protein-coupled receptor kinase 2 (GRK2), which is markedly upregulated in failing human myocardium, has been implicated as a contributing factor or consequence of heart failure (HF). Importantly, cardiac-specific GRK2 knockout mice have recently proved the pathological nature of GRK2 in HF. Targeted inhibition of GRK2 is possible using a peptide inhibitor known as the βARKct, which has rescued several disparate small animal HF models. This study was designed to evaluate long-term βARKct expression in a clinically relevant large animal HF model, using stable myocardial gene delivery with adeno-associated virus serotype 6 (AAV6).
Online publish-ahead-of-print 19 January 2012
Gesehen am 19.11.2018